Physical activity and exercise capacity in patients with moderate COPD exacerbations. Issue 2 (28th April 2016) - Alahmari, Ayedh D.; Kowlessar, Beverly S.; Patel, Anant R.C.; Mackay, Alex J.; Allinson, James P.; Wedzicha, Jadwiga A.; Donaldson, Gavin C.
Little is known about changes in physical activity during moderate (out-patient managed) exacerbations. 6-min walking distance (6MWD) was measured during 50 exacerbations when the patients were stable, and at 3 and 7 days post-exacerbation presentation. At similar time points, quadriceps maximum voluntary contraction (QMVC) was measured during 47 different exacerbations. Physical activity (SenseWear; Bodymedia Inc., Pittsburgh, PA, USA) was recorded over 2 consecutive-week periods post-presentation. 6MWD fell from a median 422 m when stable to 373 m on day 3 (p=0.001). Similarly, QMVC fell from 32.6 versus 29.7 kg (p=0.026). Falls in 6MWD were associated with a rise in C-reactive protein (r= −0.364; p=0.041) and increased Functional Assessment of Chronic Illness Therapy–Fatigue (FACIT-F) (r= −0.44; p=0.013). Light physical activity was 2.18 h·day −1 during the first week post-exacerbation and was less over week 2 (1.98 h·day −1 ; p=0.009). Patients who had attended pulmonary rehabilitation had smaller changes in 6MWD than those who had not attended (−35.0 versus −114.9 m; p=0.013). Falls in physical activity were correlated with higher depression scores (rho= −0.51; p=0.006). These findings indicate that exercise capacity and muscle strength fall at exacerbation in chronic obstructive pulmonary disease patients who are treated at home and are free to maintain normal activity. Falls in physical capacity and muscle strength during COPD exacerbations managed in the community http://ow.ly/ZtU45